Looking at ASEAN Centrality in the Amidst of TPP & RCEP Mega-Regional Competition - Aspin Nur Arifin Rivai; Gema Ramadhan Bastari (Vox Populi, 2022)
This paper attempts to understand the progressivity of economic regionalism in Southeast Asia. Unlike previous researches, this paper will explain how the complexity of Southeast Asia region affecting liberalism in ASEAN. This can be seen from how the mega-regional competition between TPP and RCEP hinders ASEAN centrality, signified by the fact that Vietnam, Singapore, Malaysia, and Brunei chose to participate in both cooperation, despite knowing that RCEP should be part of ASEAN centrality agenda. This paper will pay attention on two types of condition: (1) understanding the transformation into mega-regional partnership in Asia-Pacific; (2) understanding the decision of four ASEAN countries who choose to participate in both mega-regional models. The theory which will be used in this paper will be the ‘new trade strategy’ developed by Aggarwal and Lee (2011). In the end, this paper finds that there is a renewal in perception, interest, and domestic institution in the creation of RCEP and TPP. Meanwhile, the decision of Vietnam, Malaysia, Singapore, and Brunei to participate in both RCEP and TPP is the result of rational calculation in terms of economic advantage, political economy, domestic structure improvement, and security. These four calculations can be seen in all country, especially those who utilize greater economic liberalization.